Laser phase plate improves structure determination of small proteins by cryo-EM - Petar N. Petrov; Jessie T. Zhang; Jonathan Remis; Jeremy J. Axelrod; Hang Cheng; Eric S. Cooper; Ian K. Hicklin; Shahar Sandhaus; Cooper Schnurr; Robert M. Glaeser; Holger Müller (Science, 2026)
Phase plates can, in principle, overcome the poor image contrast in cryo–electron microscopy (cryo-EM) and the resulting limits on the structural reconstruction of small proteins. However, previous designs have been unstable and compromised the high-resolution signal and have thus been unable to surpass results achieved by standard cryo-EM. Here, we show that the laser phase plate (LPP), installed in a modern, custom Titan Krios microscope, enhances the resolution in single-particle reconstruction of small proteins by improving specimen-motion correction and recovery of information from the early frames, as well as particle visualization, three-dimensional classification, and alignment. These advances use standard defocus ranges and reconstruction procedures but open the door to LPP-tailored protocols, offering further improvements by leveraging the LPP demonstrated here.